Konsep Pancasila sebagai Sistem Filsafat : Mengapa Pancasila sebagai Sistem Filsafat - Ashfiya Nur Atqiya; Ahmad Muhamad Musta’in Nasoha; Shinta Bunga Islami; Wildan Mukti Ramadhan; Arum Budi Utami (Majelis: Jurnal Hukum Indonesia, 2024)
: Pancasila is a philosophical system that is the ideological basis of the Indonesian state. This concept represents a collection of fundamental values that have guided the formation and development of this country since its independence in 1945. Pancasila is not just a political ideology, but also a philosophical framework of thought that integrates five main principles: Belief in one Almighty God, Just and Civilized Humanity, Indonesian Unity, Democracy Led ByWisdom in Deliberation/Representation, and Sosial Justice for All Indonesian People. In this article, we will investigate the orgins, development and relevance of Pancasila in the Sosial, polotical and cultural context of Indonesian. In addition, we will explore how Pancasila as a philosophical system has shaped state policy, defined national identity, and played a role in promoting moral and ethical principles in peoples daily lives.